Associations between IL-23R gene polymorphism (rs10889677 A/C) and ankylosing spondylitis and rheumatoid arthritis susceptibility: A meta-analysis with trial sequential analysis. (18th August 2022) - Zhang, Tao; Yu, Lingxiang; Shao, Ming; Wu, Ye; Wang, Jinian; Deng, Yujie; Ni, Man; Sun, Xiaoya; Chen, Yuting; Xu, Shanshan; Ma, Yubo; Shuai, Zongwen; et al.
Abstract: Objectives: Autoimmune diseases are a kind of chronic diseases for which the immune system loses tolerance to autoantigens. This meta-analysis' purpose is to determine whether there exists a correlation between IL-23R polymorphism and common autoimmune diseases like ankylosing spondylitis (AS) and rheumatoid arthritis (RA). Methods: We searched the relevant literatures up to September 2021 and used different effect models for meta-analysis. 95% confidence interval (95% CI) and odds ratio (OR) were used to determine the relationship between rs10889677 (A/C) polymorphism and AS as well as RA. Finally, to promote the reliability of results, the trial sequential analysis (TSA) has also been applied and we searched the data related to autoimmune diseases (AS, RA) on genome-wide association studies (GWAS). Results: Generally, 31 studies were included. Rs10889677 (A/C) was significantly correlated with the susceptibility to AS and RA among the general individuals ( p < .05). Moreover, there existed a relevance between allele A and AS as well as RA in Caucasians ( p < .05). AA genotype increased the risk of autoimmune diseases in Mongolians. As a result, the robustness of meta-analysis has further been proved by TSA. Conclusion: IL-23R (rs10889677 A/C) A allele was a risk gene for AS and RA in the general population, especially in Caucasians. AA genotype increased the risk of AS and RA in Mongolians.